2003
DOI: 10.4049/jimmunol.171.8.4243
|View full text |Cite
|
Sign up to set email alerts
|

Hemozoin Increases IFN-γ-Inducible Macrophage Nitric Oxide Generation Through Extracellular Signal-Regulated Kinase- and NF-κB-Dependent Pathways

Abstract: NO overproduction has been suggested to contribute to the immunopathology related to malaria infection. Even though a role for some parasite molecules (e.g., GPI) in NO induction has been proposed, the direct contribution of hemozoin (HZ), another parasite metabolite, remains to be established. Therefore, we were interested to determine whether Plasmodium falciparum (Pf) HZ and synthetic HZ, β-hematin, alone or in combination with IFN-γ, were able to induce macrophage (Mφ) NO synthesis. We observed that neithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
118
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 64 publications
12
118
0
Order By: Relevance
“…Previous studies have proposed that both native P. falciparum hemozoin and synthetic hemozoin can induce activation of ERK 1 and 2 pathways and binding of NF-κB to the murine inducible nitric oxide synthase (iNOS) promoter, rapidly occurring within 1 h of stimulation and returning to almost basal levels after 4 h [21] . The presence of both synthetic hemozoin and interferon (IFN)-γ has been shown to act in synergy to induce NF-κB binding to the murine iNOS gene [21] .…”
Section: Effect Of Hemozoin On Blood Mononuclear Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have proposed that both native P. falciparum hemozoin and synthetic hemozoin can induce activation of ERK 1 and 2 pathways and binding of NF-κB to the murine inducible nitric oxide synthase (iNOS) promoter, rapidly occurring within 1 h of stimulation and returning to almost basal levels after 4 h [21] . The presence of both synthetic hemozoin and interferon (IFN)-γ has been shown to act in synergy to induce NF-κB binding to the murine iNOS gene [21] .…”
Section: Effect Of Hemozoin On Blood Mononuclear Cellsmentioning
confidence: 99%
“…Previous studies have proposed that both native P. falciparum hemozoin and synthetic hemozoin can induce activation of ERK 1 and 2 pathways and binding of NF-κB to the murine inducible nitric oxide synthase (iNOS) promoter, rapidly occurring within 1 h of stimulation and returning to almost basal levels after 4 h [21] . The presence of both synthetic hemozoin and interferon (IFN)-γ has been shown to act in synergy to induce NF-κB binding to the murine iNOS gene [21] . In addition, ex vivo and in vitro studies have demonstrated that significantly elevated activity of NO synthase (NOS) was found in peripheral blood mononuclear cells (PBMCs) from children with malaria anemia and that it is inversely associated with hemoglobin levels [22,23] , suggesting that hemozoin can induce NOS2 related to NO formation [22] .…”
Section: Effect Of Hemozoin On Blood Mononuclear Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several laboratories have reported a correlation between ERK activation and expression of inducible nitric oxide synthase (iNOS) in various nontransformed cells of human, rat, and murine origin (Kristof et al, 2001;Bhat and Fan, 2002;Liu et al, 2002;Jaramillo et al, 2003;Jiang et al, 2004). This cytokine-inducible enzyme is one of the three known nitric oxide synthases, which produce nitric oxide (NO) through the conversion of arginine to citrulline.…”
Section: Introductionmentioning
confidence: 99%